Water use strategies of Nitraria tangutorum in the lake-basin region of the Badain Jaran Desert - Qin, Jie; Si, Jianhua; Jia, Bing; Zhao, Chunyan; Zhou, Dongmeng; He, Xiaohui; Wang, Chunlin; Zhu, Xinglin (Frontiers in Plant Science, 2023)
Information regarding plant water-use strategies is essential for understanding the hydrological processes and plant survival adaptation mechanisms in desert lake basin regions. To examine the water use strategies of plants in desert lake basin areas, water uptake patterns, water use efficiency, and water potential of Nitraria tangutorum were investigated at different distances from the lake during the growing seasons in the lake basin regions of the Badain Jaran Desert. The results indicate that N. tangutorum primarily absorbed groundwater in May (63.8%) and August (53.5%), relied on deep soil water in June (75.1%), and uniformly absorbed soil water from different layers in July. These observations could be explained by periodic fluctuations in the groundwater level and the consequent decrease in soil water availability, as well as plant root adjustments. As soil water availability decreases, N. tangutorum adapts to water variation by increasing its water use efficiency (WUE) and reducing its leaf water potential (Ψ). With intensified water stress, N. tangutorum gradually shifted from adventurous anisohydric regulation to conservative isohydric regulation. Thus, N. tangutorum responds to diverse degrees of environmental changes by altering its water-use strategy. A better understanding of the adaptive water use strategies developed by desert plants under varying water availability conditions provides insight into the diversity of species’ reactions to long-term drought and quantifies the hydrological cycle of desert ecosystems against the background of worldwide climate warming.